The mir-34 microRNA is required for the DNA damage response in vivo in C. elegans and in vitro in human breast cancer cells - Kato, M (2009)
MicroRNAs (miRNAs) are important regulators of cell fate determination and homeostasis. Expression of these small RNA genes is tightly regulated during development and in normal tissues, but they are often misregulated in cancer. MiRNA expression is also affected by DNA damaging agents, such as radiation. In particular, mammalian miR-34 is upregulated by p53 in response to radiation, but little is known about the role of this miRNA in vivo. Here we show that Caenorhabditis elegans with loss-of-function mutations in the mir-34 gene have an abnormal cellular survival response to radiation; these animals are highly radiosensitive in the soma and radioresistant in the germline. These findings show a role for mir-34 in both apoptotic and non-apoptotic cell death in vivo, much like that of cep-1, the C. elegans p53 homolog. These results have been additionally validated in vitro in breast cancer cells, wherein exogenous addition of miR-34 alters cell survival post-radiation. These observations confirm that mir-34 is required for a normal cellular response to DNA damage in vivo resulting in altered cellular survival post-irradiation, and point to a potential therapeutic use for anti-miR-34 as a radiosensitizing agent in p53-mutant breast cancer.